Langub Civic Center - Bisares, Mae Frances A.; Del Castillo, Nicolo (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
This thesis follows site-based design. Meaning, a macro site was chosen first, then identified the issues arising, and then formed goals and objectives from there. A more specific site was located before the type of project was identified, finally forming the agenda. The chosen macro site was Davao City. The main issue identified was the lack of basic facilities especially in the hinterlands and their accessibility to them despite being a metropolitan and competitive city. The goals that were formed were based on the city's vision identified in its Comprehensive Land Use Plan (2013-2022). The main method for site selection was the plotting of existing facilities (barangay halls, schools, and health facilities). After applying a set of criteria to three (3) potential barangays, the final site identified was Barangay Langub. Based on the issues identified, the goals of the city, and the needs of the barangay, the type of project identified was a civic center. A civic center will act as the local community's central hub that will help catalyze the city's development. The agenda now is to create an accessible, self-sustaining, and cohesive center-point for Barangay Langub that can be a source of civic pride and good citizenship.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Site-based design